Correction: Helminth Colonization Is Associated with Increased Diversity of the Gut Microbiota. - Soo Ching Lee; Mei San Tang; Yvonne A L Lim; Seow Huey Choy; Zachary D Kurtz; Laura M Cox; Uma Mahesh Gundra; Ilseung Cho; Richard Bonneau; Martin J Blaser; Kek Heng Chua; P'ng Loke (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pntd.0002880.].